An in vivo strategy to counteract post-administration anticoagulant activity of azido-Warfarin - Sylvain Ursuegui (Nature Portfolio, 2017)
The interaction of long circulating drugs with biological molecules might trigger harmful side effects. Here, the authors design an anticoagulant compound that can be deactivatedin vivo using click chemistry, paving the way to the design of drugs with tunable in vivoproperties.